Pengembangan Sistem Informasi Manajemen Kepegawaian pada Yayasan Pondok Pesantren Nurul Huda Sukaraja - Rizki, Uli; Firdaus, Thoha; Widayanti, Widayanti; Irawan, Indra; Komariyah, Sri (Jurnal Nasional Ilmu Komputer, 2024)
Along with advances in information technology, the Nurul Huda Islamic Boarding School Foundation still relies on managing personnel data manually without adopting a personnel management information system. This research aims to design a personnel information system that includes employee data management, including rank, leave applications, attendance, further studies, and monitoring of employee performance. In this research, the methodology used is Extreme, which is used to model process flow. In contrast, Data Flow Diagrams (DFD) are used to model data flow in a system, helping to clearly describe processes, data, and interactions between system components. The system development method used is extreme programming. Then, the system will be tested using the Black Box Testing method. The results show that the system is 100% valid and 100% compatible.